PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT MEAD JOHNSON INDONESIA- CABANG BANJARBARU - rakhmi ridhawati; Wahyuni Tri Utami (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
His research aims to empirically proved the influence of compensation and work motivation on employee performance at PT Mead Johnson Indonesia- Banjarbaru branch. The research method used quantitative method, and data collection is carried out through questionnaires distributed directly to respondents with a total of 95 employees from several parts of the company. This study used statistical analysis tools SPSS 26.00 software. The results of the study indicated that compensation has a negative effect on employee performance at PT Mead Johnson Indonesia- Banjarbaru branch, while work motivation does not affect employee performance at PT Mead Johnson Indonesia- Banjarbaru branch. The adjusted R square value is 0.767, which indicates that the dependent variable, namely employee performance, can affect the independent variables, namely compensation and work motivation by 76.7% and the remaining 23.3% is influenced by other variables not mentioned in this study